2009
DOI: 10.1007/s10484-009-9093-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Orienting and Defensive Responses to Concealed Information: The Role of Verbalization

Abstract: Using physiological measures, concealed information can be validly assessed. Orienting theory has been proposed to account for concealed information testing. As orienting is characterized by heart rate deceleration, one would expect this type of heart rate response to concealed information. However, with some exceptions, an initial heart rate acceleration to concealed information is typically observed. In the present paper, we examine the role of verbalization to explain the mixed pattern of heart rate changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 29 publications
7
27
0
Order By: Relevance
“…However, Verschuere et al. also reported results supporting our suggestion. They conducted a within‐participant experiment by manipulating the mode of verbalization (“Yes” vs. “No” vs. “Silent”).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, Verschuere et al. also reported results supporting our suggestion. They conducted a within‐participant experiment by manipulating the mode of verbalization (“Yes” vs. “No” vs. “Silent”).…”
Section: Discussionsupporting
confidence: 90%
“…Our predictions are as follows. Differentiated responses to critical and noncritical items will be observed not only in SCR, but also in cardiopulmonary measures because those responses were observed even in the silent condition when questions were presented . On the other hand, differentiated responses accompanying answers will not be observed in SCR because this did not happen in Furedy and Ben‐Shakhar .…”
mentioning
confidence: 98%
“…The higher the proportion of irrelevant items relative to probe items, the greater the SCR CIT effect [Ben-Shakhar, 1977;Ben-Shakhar et al, 1982;Lieblich et al, 1970]. Others, however, could not replicate these findings [Kugelmass et al, 1967;Verschuere et al, 2009a], and in two meta-analyses on moderators of the SCR CIT effect, the factor deception failed to reach significance [Ben-Shakhar and Elaad, 2003;Meijer et al, 2014]. Some researchers found that when guilty suspects were required to actively deceive during the test (i.e., deny probe knowledge by responding "No" to every item) the SCR CIT effect was larger compared to when suspects were not required to actively deceive [i.e., give no responses or respond "Yes" to every item; see e.g., Elaad and Ben-Shakhar, 1989;Furedy and Ben-Shakhar, 1991;Gustafson and Orne, 1965;Horneman and O'Gorman, 1985].…”
Section: Introductionmentioning
confidence: 98%
“…Finally, Ambach, Stark, Peper, and Vaitl (2008b) examined the effect of overt deception on the CIT's outcomes by requiring their participants to answer either deceptively or truthfully four seconds after item presentation (see also Verschuere, Crombez, Smolders, & De Clercq, 2009). Specifically, participants were motivated through the promise of a reward to perform the CIT task as well as possible.…”
mentioning
confidence: 99%